1985
DOI: 10.1093/infdis/152.5.895
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection of Human Mononuclear Leukocytes in Vitro and in Vivo

Abstract: Recurrent infections with respiratory syncytial virus (RSV) have been well documented despite serological evidence of prior exposure of the host and the absence of clear evidence of antigenic variation of the virus. Therefore, human mononuclear leukocytes, as well as purified lymphocytes and monocytes-macrophages, were exposed to RSV in vitro and examined for expression of viral antigens by using indirect immunofluorescence with monoclonal antibodies to RSV. RSV infected both human monocytes-macrophages and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…Recently, RS virus has been shown to replicate in vitro in human peripheral blood mononuclear leukocytes (Krilov et al, 1987). In addition, RS virus antigen has been found in circulating mononuclear leukocytes of infants with RS virus infections (Dumorat et al, 1985). The present report describes the infection of the U937 human macrophage cell line by RS virus and the occurrence of virus-enhancing antibodies in human sera.…”
mentioning
confidence: 74%
“…Recently, RS virus has been shown to replicate in vitro in human peripheral blood mononuclear leukocytes (Krilov et al, 1987). In addition, RS virus antigen has been found in circulating mononuclear leukocytes of infants with RS virus infections (Dumorat et al, 1985). The present report describes the infection of the U937 human macrophage cell line by RS virus and the occurrence of virus-enhancing antibodies in human sera.…”
mentioning
confidence: 74%
“…Detection of BRSV was based on data published on the related HRSV Studies on HRSV showed that in vitro the virus propagates in blood monocytes and alveolar macrophages (Domurat et al 1985;Midulla et al 1989). Viral mRNA was isolated from circulating mononuclear cells of children developing signs of respiratory infection (O'Donnell et al 1989) and HRSV genome was demonstrated by PCR in blood samples (Rohwedder et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro have shown that Sendal virus inhibits the ability of peripheral blood monocytes to enhance lymphocyte transformation to phytohaemaggtutinin and leads to significant interferon ~ (HulFN-~) production by monocytes, whereas RSV did not affect either of these monocyte functions (Chonmaitree et al, 1981 ;Morahan et al, 1985). Despite this lack of effect on monocytes, RSV has recently been shown to be capable of infecting human peripheral blood monocytes in vitro and RSV antigen has been found in circulating monocytes of infants with RSV disease (Domurat et al,, 1985).…”
Section: Discussionmentioning
confidence: 99%